Association between nutrient patterns and serum lipids in Chinese adult women: A cross‐sectional study. Issue 2 (19th October 2018) - Zhang, Jian; Tan, Shengjie; Zhao, Ai; Wang, Meichen; Wang, Peiyu; Zhang, Yumei
Abstract : Aim: To investigate the association between patterns of nutrient intake and serum lipids in Chinese women aged 18–80 years. Methods: In the present study, cross‐sectional data were analysed from 2886 female participants aged 18–80 years from the China Health and Nutrition Survey wave 2009. Nutrient patterns were identified using factor analysis combined with cluster analysis based on the data of nutrient intake for three consecutive days. Multivariate linear regression models were used to estimate the association of nutrient patterns with serum lipids. Results: Four nutrient patterns were identified in Chinese adult women, which were the plant‐based pattern, carbohydrate and animal fat pattern, plant fat and sodium pattern, and the animal‐based pattern. Participants following different patterns varied significantly in sociodemographic characteristics, lifestyle behaviours and food consumption. Compared with the plant‐based pattern, the carbohydrate and animal fat pattern was positively associated with low‐density lipoprotein cholesterol ( β  = 4.57, 95% CI: 0.29–8.85, P  = 0.036) and total cholesterol ( β  = 4.89, 95% CI: 0.34–9.44, P  = 0.035). The corresponding rises for the animal‐based pattern were 4.91 (95% CI: 0.99–8.82, P  = 0.014) and 4.98 (95% CI: 0.82–9.15, P  = 0.019), respectively. Conclusions: Nutrient patterns with a high intake of animal fat and a low intake dietary fibre and with high intakes of animal fat, animal protein and cholesterol may increase the serum cholesterol in Chinese women.